(untitled) (American AgriTech: Journal of Agricultural Technology Innovation and Sustainability, 2026)
The article describes the information about the drive of bovicoliosis, one of the most prevalent ectoparasitic diseases among goats in recent years. Maqolada keyingi yillarda echkilar orasida eng ko‘p tarqalayotgan ektoparazitlardan junxo‘rlar haqidagi ma’lumotlar bayon etilgan